Computer Aided Design and Multiple Coupled Circuit Modelling of BDFM - Chaouche Saad (3rd International Conference on Control, Engineering & Information Technology CEIT, 2015)
A general and efficient algorithmic implementation is presented for calculating of self and/or mutual inductances using winding function theory for any type of stator and/or rotor layout slot windings. Then, this algorithm is applied on brushless doubly fed induction machines with standard cage. In fact, several kinds of slot windings are treated to prove the efficiency of this technique. The procedure is provided with inputs vector consisted by the machine main dimensions, air gap length, stator and rotor slot numbers, pole pairs, slots per pole and phase and the winding slots sequence defining the winding kind. Consequently, the application of this procedure yields both self and mutual inductances matrix of the stator and the rotor as well as the stator-rotor mutual inductances curve and its derivative. Finally, a dynamic simulation with multiple coupled circuits modelling is carried out and the results are presented and discussed.